2010
DOI: 10.1126/science.1177132
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Iapetus’ Extreme Albedo Dichotomy by Exogenically Triggered Thermal Ice Migration

Abstract: Iapetus Revealed The striking appearance of Saturn's moon Iapetus—half black and half white—has puzzled astronomers for over three centuries. Now Spencer and Denk (p. 432 , published online 10 December) present an explanation for this asymmetry: A thermally controlled runaway migration of water ice triggered by exogenic deposition of dark material on the moon's leading darker side, which faces the direction of motion of the moon in its orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 36 publications
1
88
2
Order By: Relevance
“…The origin of the material that causes the albedo dichotomy of Iapetus has been the subject of a long standing debate (Buratti and Hicks, 2003;Spencer and Denk, 2010;Tosi et al, 2010). However, Clark et al (2008Clark et al ( , 2011b, showed that the visible colors and UV absorber are consistent with a single source with varying abundance of the contaminants.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…The origin of the material that causes the albedo dichotomy of Iapetus has been the subject of a long standing debate (Buratti and Hicks, 2003;Spencer and Denk, 2010;Tosi et al, 2010). However, Clark et al (2008Clark et al ( , 2011b, showed that the visible colors and UV absorber are consistent with a single source with varying abundance of the contaminants.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…The albedo value of Iapetus' leading side (∼0.04) reported by Spencer & Denk (2010) is in the range of the typical albedo values of F-type asteroids, i.e., 0.03-0.07 (Tedesco et al 2002). However, the polarization minimum of Iapetus' leading side is slightly shallower than the typical value for low-albedo asteroids, which is ∼−1.6%, and slightly deeper than that of the F-type asteroid 419 Aurelia, which is ∼1.0% (Belskaya et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…A thermal model of the evolution of Iapetus' surface (Spencer & Denk 2010), in which H 2 O ice is mobilized by the higher temperatures in the dark hemisphere and re-condensed elsewhere, convincingly reproduces the albedo pattern seen today. An absorption band at 3.28 μm, attributed to polycyclic aromatic hydrocarbons, has been identified in the low-albedo material on Iapetus (Cruikshank et al 2008).…”
Section: Polycyclic Aromatic and Aliphatic Hydrocarbons On Saturn's Smentioning
confidence: 87%